Malaria Vaccine Development: Focusing Field Erythrocyte Invasion Studies on Phenotypic Diversity: The West African Merozoite Invasion Network (WAMIN). Issue 4 (April 2016) - Ahouidi, Ambroise D.; Amambua-Ngwa, Alfred; Awandare, Gordon A.; Bei, Amy K.; Conway, David J.; Diakite, Mahamadou; Duraisingh, Manoj T.; Rayner, Julian C.; Zenonos, Zenon A.; ,
Abstract : Erythrocyte invasion by Plasmodium falciparum merozoites is an essential step for parasite survival and proliferation. Invasion is mediated by multiple ligands, which could be promising vaccine targets. The usage and sequence of these ligands differs between parasites, yet most studies of them have been carried out in only a few laboratory-adapted lines. To understand the true extent of natural variation in invasion phenotypes and prioritize vaccine candidates on a relevant evidence base, we need to develop and apply standardized assays to large numbers of field isolates. The West African Merozoite Invasion Network (WAMIN) has been formed to meet these goals, expand training in Plasmodium phenotyping, and perform large-scale field phenotyping studies in order to prioritize blood stage vaccine candidates. Trends: Merozoite invasion is a promising vaccine target. Studies of invasion in the field will be essential to advance vaccine development. A new network, WAMIN, has been formed to optimize and standardize invasion assays. WAMIN will prioritize vaccine targets by phenotyping thousands of field parasites.